2017
DOI: 10.1016/j.otsr.2017.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Acute finger-tip infection: Management and treatment. A 103-case series

Abstract: Hospital admission, operative treatment under general anesthesia, and AT are factors exacerbating cost and increase the management burden of AFTI. Treatment in emergency consultation seems perfectly feasible. AT does not seem useful in the absence of severe comorbidities if resection is complete. Analysis of bacterial susceptibility and renewal of the initial dressing at 1 week enable progression to be monitored and treatment changed as necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
4

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
4
0
4
Order By: Relevance
“…Though rarely, complications such as osteomyelitis, sepsis and pericarditis secondary to paronychia have been reported in the literature (22,23). This group of patients is monitored with closer follow-ups in our clinical practice due to the risk of systemic infection and septicemia in patients with immunodeficiency (1,2,16,24). Cellulite secondary to paronychia was determined to have developed in the feet of three patients in this study.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Though rarely, complications such as osteomyelitis, sepsis and pericarditis secondary to paronychia have been reported in the literature (22,23). This group of patients is monitored with closer follow-ups in our clinical practice due to the risk of systemic infection and septicemia in patients with immunodeficiency (1,2,16,24). Cellulite secondary to paronychia was determined to have developed in the feet of three patients in this study.…”
Section: Discussionmentioning
confidence: 71%
“…In a study by Rabarin et al with 103 cases with acute finger infections, it has been reported that all received drainage, 23.3% received antibiotics additionally, 3.8% of the patients underwent chemotherapy, 1.9% had diabetes mellitus, 0.9% had a diagnosis of scleroderma, and 0.9% had been using steroids (16). The same publication has also pointed out that the success of especially surgery and/or antibiotherapy was discussed, all patients recovered without sequalae, and that the most frequently isolated microorganisms were methicillin-susceptible Staphylococcus aureus (MSSA) and polymicrobial microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Rabarin ve arkadaşları yaptığı çalışmada, akut parmak enfeksiyonu alan 103 olgu ele alınmış, tamamına drenaj yapılmış, %23.3'ünün ilaveten antibiyoterapi aldığı, hastaların %3.8'inin kemoterapi aldığı, %1.9'unun diabetes mellitus, %0.9'unun skleroderma tanısı olduğu ve %0.9'unun ise steroid almakta olduğu rapor edilmiştir (16). Aynı yayında, özellikle cerrahi ve/veya antibiyoterapinin tedavi başarısı tartışılmış olup, tüm hastalar sekelsiz iyileşmiş ve en sık izole edilen mikroroganizmalar metisilin duyarlı Staphylococcus aureus (MSSA) ve polimikrobiyal mikroroganizmalar olarak rapor edilmiştir.…”
Section: Discussionunclassified
“…Paronişiye ikincil nadir de olsa osteomiyelit, sepsis ve perikardit gibi komplikasyonlar literatürde bildirilmiştir (22,23). Özellikle immünyetmezliği olan hastalarda sistemik enfeksiyon ve septisemi riski nedeni ile bu grup hastalar, klinik pratiğimizde daha yakın kontrollerle izlenmektedir (1,2,16,24). Bu çalışmada üç hastanın ayağında paronişiye sekonder sellülit geliştiği tespit edilmiştir.…”
Section: Discussionunclassified
“…Rabarin und Mitarb. [14] konstatieren, dass bei einer gründlichen Resektion bei fehlenden Komorbiditäten eine Antibiotikatherapie nicht notwendig sei, differenzieren aber bei ihren 103 Patienten nicht das Infektionsstadium.…”
Section: Operatives Vorgehenunclassified